Characteristics of older-patient-specif ic oncological trials: a cross-sectional analysis of ClinicalTrials.gov. (14th April 2022) - Yang, Yun; Xie, Mingxing; Zhang, Li; Yu, Kaixu; Li, He; Sun, Wei; Feng, Zishan; Tang, Yun; Ma, Haotian; Wang, Qingpeng; Wu, Gang; Yang, Kunyu; et al.
Abstract: Background: clinical trials dedicated to the older patients with cancer are essential to help to define optimal cancer therapy for this rapidly growing population. Our study aimed to analyse the characteristics and the evolution of older-patient-specific oncological trials registered in ClinicalTrials.gov. Methods: a dataset of 61, 120 oncological trials registered in ClinicalTrials.gov between 2000 and 2019 was downloaded. Characteristics of older-patient-specific trials were compared with characteristics of age-unspecified trials. Chronological shifts in older-patient-specific trials were also analysed. Results: of the 49, 273 interventional trials eligible for analysis, only 490 (1.0%) were older-patient-specific. More than half of the older-patient-specific trials were phase 2 and enrolled less than 100 patients. Compared with age-unspecified trials, older-patient-specific trials were less likely to be funded by industry (26.9 vs 37.1%), and more likely to be conducted in Europe (44.5 vs 28.3%). During the two time periods between 2000 and 2009, and 2010 and 2019, the proportion of supportive care-oriented trials increased from 1.9 to 13.9%. Concerningly, the use of clinically meaningful end points in older patients such as disease-specific survival, patient-reported outcomes and functional status as a primary end point was uncommon (0.4, 8.1 and 7.3%, respectively). There was no correlation between the number of trials for a given cancer type and relative incidence and mortality. 196/490 (40.0%) of the trials were conducted for patients with haematological cancer. Conclusion: our study helps us to better understand the current state of older-patient-specific oncological trials and provide insights for future development, resulting in the improvement of the care of older patients with cancer.